BERTAHAN DI TENGAH SAMUDRA: PANDANGAN ETNOBOTANI TERHADAP PULAU ENGGANO, ALAM, DAN MANUSIANYA - Royyani, Mohammad Fathi; Lestari Sihotang, Vera Budi; Efendy, Oscar (Perhimpunan Biologi Indonesia, 2018)
ABSTRACTThe objective of study was to explore Enggano?s people live survival strategy ulilizing plant resources . To enable living in Enggano, local community utilize plant resources with diverse strategy. The main argument of their article is social and enviromental changes affect on the utilization of plant resources as the main strategy of survival. There strategies of data collection were applied to verify the local community survival strategy. Namely: FGD, questionair and interview. So we observed society change their live strategy on plant resources utilization in accordance with social change. New access on information, migration, to other island influence on society orientaton. From live survival strategy to economic benefit. Keywords: Enggano, plants, social change, survival, useful.